2006
DOI: 10.1007/s00404-006-0259-3
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous delivery is related to barometric pressure

Abstract: A causal relationship was noted between the number of rupture of the fetal membranes, delivery and barometric pressure, suggesting that low barometric pressure induces rupture of the fetal membranes and delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 9 publications
0
23
0
Order By: Relevance
“…Five studies examined barometric pressure [65,71,72,73,74]. One large study conducted in England (482,765 births) [65] reported no association of preterm birth with daily mean barometric pressure, or with the largest daily drop in barometric pressure.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies examined barometric pressure [65,71,72,73,74]. One large study conducted in England (482,765 births) [65] reported no association of preterm birth with daily mean barometric pressure, or with the largest daily drop in barometric pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies focused on labor onset [72,73,74], but could not be pooled because of the heterogeneity in the definition of categorical variables for barometric pressure. A small USA study (162 births) reported a significantly higher occurrence of labor onset in the day following, than preceding a drop in barometric pressure (defined as ≥0.06 inches of mercury in 24 h) [74].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…King et al (1997), in Texas, USA, found an increased rate of labor onset associated with reductions in atmospheric pressure in a sample of 162 patients. In a study of 2,278 women in Tokyo, Japan, increases of rates of the rupture of membranes and childbirth were correlated with a reduction in the atmospheric pressure (Akutagawa et al 2007). In Illinois, USA, Hirsch et al (2010) used logistic regression models to associate onset of labor and meteorological variables such as atmospheric pressure, temperature and humidity.…”
Section: Discussionmentioning
confidence: 97%
“…However, the scientific data concerning lunar influence upon labor admissions are controversial. Although climatic conditions, predominantly atmospheric pressure, have been reported to be factors that influence labor (Akutagawa et al 2007;Driscoll 1995;Hirsch et al 2010;King et al 1997;Noller et al 1996), there have been few studies using multivariate analysis with which to assess this association.…”
Section: Introductionmentioning
confidence: 97%